2015
DOI: 10.1001/jamadermatol.2014.3456
|View full text |Cite
|
Sign up to set email alerts
|

Combining Biologic Therapies With Other Systemic Treatments in Psoriasis

Abstract: Among appropriately selected patients with psoriasis, carefully chosen combinations may result in greater efficacy, while minimizing toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Biologic agents have been approved by the FDA to treat moderate to severe psoriasis that not responded to an adequate trial of one or more of the traditional drugs. Biologic therapies are most effective in the treatment of psorisis [32], but a percentage of no-responder patients still exists. Moreover, disadvantages are represented by their possible side effects and limited availability of long-term safety data.…”
Section: Introductionmentioning
confidence: 99%
“…Biologic agents have been approved by the FDA to treat moderate to severe psoriasis that not responded to an adequate trial of one or more of the traditional drugs. Biologic therapies are most effective in the treatment of psorisis [32], but a percentage of no-responder patients still exists. Moreover, disadvantages are represented by their possible side effects and limited availability of long-term safety data.…”
Section: Introductionmentioning
confidence: 99%
“…In daily practice MTX is more frequently combined with biologics than fumarates, because it is assumed that (low-dose) MTX increases the clinical efficacy of biologics by reducing the development of antidrug antibodies [23,24]. Anti-etanercept antibodies have only sporadically been observed in clinical studies, indicating that loss of clinical efficacy for etanercept is probably caused by other, yet unidentified factors [25].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, data from recent European reports indicate that biological therapy is given concomitantly with traditional systemic drugs in up to 30% of patients with psoriasis . Combination therapy of ciclosporin A with biological drugs, particularly etanercept and adalimumab, has been rarely reported in the literature, including in nonrandomized trials and case reports . However, in a review of the literature we found no studies reporting combination therapy of ciclosporin A and infliximab, except for short overlapping periods during switching or sequential therapy…”
Section: Main Patient Characteristics At Baseline and During Follow‐upmentioning
confidence: 93%